SIMULASI DAN PERHITUNGAN SPIN ROKET FOLDED FIN BERDIAMETER 200 mm - Ahmad Jamaludin Fitroh; - Saeri (National Institute of Aeronautics and Space - LAPAN, 2010)
One of rocket movement types is spin maneuver. The rocket rotation towards the axisymmetric axis is needed so the rocket can move straight in it’s flight line. The object of spin simulation and calculation in this work is the Rocket of LAPAN with the diameter of 200 mm. The simulation and calculation were done for 0.6, 1.0, 2.0, and 3.0 Mach of flight speed. The simulation and calculation results show that spin and drag of fin will increase while the flight speed is increasing. The spin and drag of fin for 3.0 Mach of flight speed are 36 rps and 16.6 kg respectively